2017
DOI: 10.1080/10934529.2017.1368305
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-individual variation in urinary concentrations of parabens in male and female Japanese subjects

Abstract: We evaluated the representativeness of concentrations of parabens in a spot urine sample for the assessment of long-term exposure levels. Urine sample was taken monthly from 10 male Japanese subjects (35.9 ± 6.8 years) and 12 female Japanese university students (21.1 ± 0.4 years) for 5 months and measured for methyl (MP), ethyl (EP), propyl (PP) and butyl (BP) parabens by liquid chromatography-tandem mass spectrometry. Median (min-max) specific-gravity-adjusted urinary concentrations of the male group (n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In terms of our study, this hypothesis would help explain why being female was associated with lower triglyceride concentrations when exposed to methylparaben, ethylparaben, or propylparaben and why those participants with a greater BMI did not have that association. It is also consistent with previous research that has found higher concentrations of various parabens in females [ 2 , 3 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of our study, this hypothesis would help explain why being female was associated with lower triglyceride concentrations when exposed to methylparaben, ethylparaben, or propylparaben and why those participants with a greater BMI did not have that association. It is also consistent with previous research that has found higher concentrations of various parabens in females [ 2 , 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to urine, parabens have often been detected in human cells, milk, and tissue samples [ 1 5 ]. Several studies have associated urinary paraben levels with personal care product usage [ 1 3 ]. Furthermore, a study conducted in trauma victims found methylparabens in the bulk of their urine and serum samples [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low ICCs were obtained for two random spots (ICCs < 0.30) (Engel et al, 2014) and two 24 h urine samples (ICCs < 0.42) (van der Meer et al, 2021) collected from adults at least two years apart. Higher ICCs were reported in other longitudinal studies in which repeated spot samples were provided by non-pregnant women and male adults over less than five months (ICCs 0.28-0.68) (Dewalque et al, 2015;Nishihama et al, 2018;Pollack et al, 2016). However, lower variability for MeP and EtP was observed in men (ICCs 0.56-0.58) than women (ICCs 0.40-0.43) (Dewalque et al, 2015;Nishihama et al, 2018;Pollack et al, 2016) which may be due to a different pattern of PCPs use.…”
Section: Variability In Paraben Concentrationsmentioning
confidence: 60%
“…In total, 17 studies describing temporal variability in urinary excretion of parabens in general population (Dewalque et al, 2015;Engel et al, 2014;Huang et al, 2021;Kim et al, 2020b;Koch et al, 2014;Nishihama et al, 2018;Pollack et al, 2016;Sakhi et al, 2018;Smith et al, 2012;van der Meer et al, 2021), pregnant women (Casas et al, 2018;Guidry et al, 2015;Li et al, 2019b;Meeker et al, 2013a;Philippat et al, 2013;Vernet et al, 2018;Yazdy et al, 2018) and children (Casas et al, 2018;Kim et al, 2020b) were retrieved from the literature search. ICCs for two parabens (MeP and PrP) were reported in all studies.…”
Section: Variability In Paraben Concentrationsmentioning
confidence: 99%
“…Parabens are non-persistent compounds that have short half-lives of about 4-8 h in the human body [12]. While urinary paraben levels fluctuate over time, humans are consistently exposed to parabens through numerous sources in daily lives [13,14]. Several nation-wide biomonitoring programs have shown the widespread occurrences of these chemicals in humans.…”
Section: Introductionmentioning
confidence: 99%